Species specificity of renin kinetics in transgenic rats harboring the human renin and angiotensinogen genes - Ganten, Detlev; Wagner, J.; Zeh, K.; Bader, Michael; Michel, J. B.; Paul, M.; Zimmermann, F.; Ruf, P.; Hilgenfeldt, Ulrich; Ganten, Ursel (Proceedings of the National Academy of Sciences of the United States of America, 1992)
The renin-angiotensin system (RAS) is the most important regulatory system of electrolyte homeostasis and blood pressure. We report here the development of transgenic rats carrying the human angiotensinogen TGR-(hAOGEN) and human renin TGR(hREN) genes. The plasma levels and tissue distribution of the transcription and translation products from both genes are described. A unique species specificity of the enzyme kinetics was observed. The human RAS components in the transgenic rats did not interact with the endogenous rat RAS in vivo. Instead, infusions of exogenous human RAS components specifically interacted with human transgene translation products. Thus, infusion of human renin in TGR(hAOGEN) led to an increase of angiotensin II and an elevation of blood pressure, which could not be antagonized by the human-specific renin enzyme inhibitor Ro 42-5892. Rat renin also elevated blood pressure and angiotensin II in TGR(hAOGEN); however, this effect was not antagonized by the human renin inhibitor. Compared to mice, rats offer the advantage of chronic instrumentation and repetitive, sophisticated, hemodynamic, and endocrinological investigations. Thus, transgenic rat models with human-specific enzyme kinetics permit primate-specific analyses in non-primate in vivo and in vitro experimental systems.
Gesehen am 05.12.2023